Spillover effects between green bond markets and major financial markets - Ding, Yuhan; An, Zhiyu (Transactions on Economics, Business and Management Research, 2024)
The study of spillover effects between the green bond market and major financial markets is of guiding significance for the development of a strong and sustainable green financial system to help realize the national goals of carbon peaking and carbon neutrality. This paper constructs the spillover index matrix through generalized vector autoregression and prediction error variance decomposition, studies the static and dynamic spillover between the green bond market and other major financial markets from the perspective of time and frequency domains, and further explores the mechanism and law of the spillover effect through the construction of the spillover network structure diagram. The conclusion is that there is a strong spillover effect between the green bond market and other major financial markets, which is asymmetric, and the spillover effect of negative return series is stronger than that of positive return series. In addition, the spillover effects among markets are strongest in the short term and gradually weaken in the medium and long term, and will be stronger in the case of high market uncertainty, such as the New Crown Pneumonia outbreak.